2018
DOI: 10.1002/jum.14828
|View full text |Cite
|
Sign up to set email alerts
|

Medial and Lateral Patellofemoral Joint Retinaculum Thickness in People With Patellofemoral Pain: A Case‐Control Study

Abstract: Objectives To measure the medial and lateral retinaculum thickness in individuals with and without patellofemoral pain using ultrasound and to assess associations with the symptom duration and function. Methods Medial and lateral patellofemoral joint retinaculum thicknesses of 32 knees (16 with patellofemoral pain and 16 asymptomatic) were measured with B‐mode ultrasound at 0.5, 1, and 1.5 cm from the patella border. Participants with patellofemoral pain completed a Kujala questionnaire, and both groups underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…neovascularization, hyperinnervation, and thickening) and bone of the patella J o u r n a l P r e -p r o o f (e.g. increased intraosseous pressure and decreased arterial blood flow of the patella) were described previously (Dye, 2005;Lack et al, 2018a;Miltner et al, 2003;Näslund et al, 2007;Sanchis-Alfonso, 2014;Schoots et al, 2013). Those changes may be mediated by reduced soft tissue flexibility as a result of structural and inflammatory changes in long-standing PFP (Arnoldi, 1991;Zügel et al, 2018).…”
Section: Introductionmentioning
confidence: 77%
“…neovascularization, hyperinnervation, and thickening) and bone of the patella J o u r n a l P r e -p r o o f (e.g. increased intraosseous pressure and decreased arterial blood flow of the patella) were described previously (Dye, 2005;Lack et al, 2018a;Miltner et al, 2003;Näslund et al, 2007;Sanchis-Alfonso, 2014;Schoots et al, 2013). Those changes may be mediated by reduced soft tissue flexibility as a result of structural and inflammatory changes in long-standing PFP (Arnoldi, 1991;Zügel et al, 2018).…”
Section: Introductionmentioning
confidence: 77%
“…Unfortunately, the lateral retinaculum can often exceed medial forces leading to lateral deviation of the patella and thus maltracking. Studies have shown an association with of IT band and lateral retinaculum thickness and tightness to be increased in patient with patellofemoral pain than those without, ultimately leading to patellar maltracking [8][9][10][11][12].…”
Section: Anatomical Considerationsmentioning
confidence: 99%
“…However, if the lateral retinaculum is too taut, theoretically lateral forces overcome medial forces leading to patellar maltracking. When studies have looked at the association of IT band and the lateral retinaculum, they have found it to be tighter and thicker than that of patients without patellofemoral pain, contributing to altered patellar kinematics [32][33][34][35][36].…”
Section: Flexibility/inflexibilitymentioning
confidence: 99%
“…It has been shown that persons with PFP have a tighter and thicker iliotibial band compared with pain-free controls. In vivo and cadaveric studies confirm that iliotibial band tension has a significant impact on patellar alignment and tracking, although it is not clear if this tightness and thickening is an adaption to or a cause of patellar lateral tilt [32][33][34][35][36]. Unfortunately, research has not shown stretching alone to be effective and deep soft tissue mobilization may be needed.…”
Section: Flexibilitymentioning
confidence: 99%